2014
DOI: 10.1007/s10163-014-0297-z
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of granulated lead slag as a structural material in roads constructions

Abstract: Pyrometallurgical processing of lead ores generates large amounts of slag which is stockpiled as chunk or granules. Romanian dump heaps of such slag produced in the period 1972-1998, occupy an area of 4522 m 2 and a volume of 6616 m 3 . To assess the possibility of using this material in road construction, a complex characterisation of this waste has been carried out. X-ray diffraction, microcompositional and microstructural analysis revealed the presence of Fe, Zn, Pb, Cu sulfides, Fe, Ca, Si oxides and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
1
Order By: Relevance
“…For PC2, As is associated with soil parent materials [64], which can explain why the content of As in soils was higher than that in street dust. Cu is key component of building materials [65,66] and Hg is widely used in pesticides, such as thermometers [67,68,69]. Coal combustion is one of the main sources of Hg in Shanxi province [36,70].…”
Section: Discussionmentioning
confidence: 99%
“…For PC2, As is associated with soil parent materials [64], which can explain why the content of As in soils was higher than that in street dust. Cu is key component of building materials [65,66] and Hg is widely used in pesticides, such as thermometers [67,68,69]. Coal combustion is one of the main sources of Hg in Shanxi province [36,70].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using industrial by-products as integral substitutes of the natural aggregate in the production of cement bound granular materials for road foundations was also verified (Pasetto et al, 2015). In addition, utilization of granulated lead slag as a structural material in roads constructions is suitable under certain conditions (material for road base (subbase) under a waterproof coating such as asphalt, at least 0.5 meter above the phreatic water level) (Buzatu et al, 2015). Finally, utilization of steel slag as coarse aggregate substitute in surface courses appeared technically appropriate and could enhance the engineering properties of asphalt mixtures (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Primary and secondary lead slag can be turned both in fine and coarse aggregates through a cement-based stabilization/solidification process [84]. It has shown a better grain size curve than sand itself, complying with the compressive strength requirements [85]. Alwaeli [86] has demonstrated that the incorporation of granulated lead-zinc slag in concrete works as a shield to the gamma radiation, so it would properly fit in laboratories construction where radiation are generally used.…”
Section: Metallurgical Industry By-productsmentioning
confidence: 99%